Deixis as a Significant Element of Human Communication - Yelena Yerznkyan (Armenian Folia Anglistika, 2009)
The article attempts to reveal the semantic characteristics of deixis that determine the role of deictic words in the process of communication. Deixis is viewed as a means of linguistic nomination that points out the main elements of the communication act – the place, time, the speaker and the hearer. Deictic words link two different situations – content (what is stated) and speech, extralinguistic (when, where, and by whom the communication is realized).